Estruturas de governança na compra de laranja pelos packing houses de São Paulo : um estudo multicaso - Neves, Marcelo Costa Marques (2012)
Several studies related to agribusiness were developed trying to explain existing transactions in different agroindustrial complexes. Brazil has significant equity in the provision of products of the agroindustrial complex citrus, holding 30% of world production and moving about $ 15 billion, highlighting the state of São Paulo, holder of 70% of the planted area in the country. One of the segments understudied in the complex is the fresh fruit market, which is well developed in countries like Argentina, Italy, Spain and South Africa, and Brazil still needs to develop. Therefore, the aim of this work was through a multicase study to show the main governances used by São Paulos´s packing houses. Using Transaction Cost Economics theory, we analyzed the coordination established between the packing house and its suppliers of orange. Interviews were conducted with six packing houses distributed by the main citrus regions of the state of São Paulo. As a result it was found that the most representative governance structure present was hybrid, which has being established by agreements characterized as relational, more flexible and not formalized.